Acreditación universitaria - Silva Merino, Jorge (2011)
The present article is about the accred it at ion as a result of a quality assurance process from the externa evaluation, which purpose is to lead the university instit ut ion int o the application of an instit ut iona l imp rovement program. The starting point of this process is the s lf - evaluation which reinforce process of research and planning with a rationalization of ali the components in order to assure that educational policies and regulations wil l guarantee the qua l it y improvement .